Energetic and Metabolic Power Demands of National Rugby League Match-Play - Cummins, C.; Gray, A.; Shorter, K.; Halaki, M.; Orr, R. (International Journal of Sports Medicine, 2016)
The purpose of this study was to apply a time-motion model to estimate and describe the energy expenditure and metabolic power demands of playing positions in elite rugby league match-play, utilizing Global Positioning System (GPS) devices. 18 elite rugby league players participated in this study. Players’ positional groups included: outside backs (n=59 files, n=4 players), adjustables (n=74 files, n=4 players), wide-running (n=104 files, n=7 players) and hit-up forwards (n=36 files, n=3 players). Outside backs expended the greatest total energy (40.1±5.0 kJ·kg−1) per match, equivalent to 8.1%, 26.6% and 61.9% greater energy than adjustables, wide-running and hit-up forwards, respectively. Adjustables attained an anaerobic index 7.3% higher than wide-running forwards, 19.7% higher than hit-up forwards (p=0.001) and 43.2% higher than outside backs (p<0.001). Wide-running forwards achieved an anaerobic index (0.34±0.04) 11% and 32.8% higher than hit-up forwards (p=0.001) and outside backs (p<0.001), respectively. Mean power of adjustables (10.0±0.9 W·kg−1) was significantly higher than all other groups (outside backs: 28.8%, 7.8±1.0; hit-up: 12.4%, 8.9±0.6; and wide-running: 8.7%, 9.2±0.7 forwards) (p<0.001). Energetics indices indicated differing metabolic demands for all positional groups, suggesting position-specific conditioning drills are required to replicate the energetic demands of match-play.
Keywords: energy cost; metabolic demands; match analysis; global positioning system (GPS); rugby league